The distinct link of perfectionism with positive and negative mental health outcomes - Simon, Patricia D.; Salanga, Maria Guadalupe C.; Aruta, John Jamir Benzon R. (Frontiers in Psychiatry, 2025)
Perfectionism is a known risk for mental health symptoms. However, the literature on perfectionism and mental health mostly focused on the psychopathological symptoms when mental health is not only about the absence of psychopathology but also the presence of positive indicators. The present study aimed to examine the associations of adaptive and maladaptive dimensions of perfectionism with bidimensional mental health among undergraduate students (N = 467) at a private university in the Philippines. We assessed the role of High Standards and Discrepancy perfectionism on the negative (depression, anxiety, and stress) and positive (satisfaction with life and meaning in life) indicators of mental health. Structural equation modeling demonstrated distinct associations of High Standards and Discrepancy on mental health and well-being outcomes. High Standards positively predicted stress and life satisfaction, and negatively predicted depression, presence of meaning, and search for meaning. High Standards did not have a significant effect on anxiety. Discrepancy positively predicted depression, anxiety, and stress and negatively predicted life satisfaction. Interestingly, presence of meaning was significantly and positively associated with Discrepancy while search for meaning was not. This study contributes to the literature by finding evidence for the distinct influence of Discrepancy and High Standards on several indicators of positive and negative mental health.